Chronic neurodegeneration induces type I interferon synthesis via STING, shaping microglial phenotype and accelerating disease progression. Issue 7 (25th January 2019) - Nazmi, Arshed; Field, Robert H.; Griffin, Eadaoin W.; Haugh, Orla; Hennessy, Edel; Cox, Donal; Reis, Renata; Tortorelli, Lucas; Murray, Carol L.; Lopez‐Rodriguez, Ana Belen; Jin, Lei; Lavelle, Ed C.; et al.
Abstract: Type I interferons (IFN‐I) are the principal antiviral molecules of the innate immune system and can be made by most cell types, including central nervous system cells. IFN‐I has been implicated in neuroinflammation during neurodegeneration, but its mechanism of induction and its consequences remain unclear. In the current study, we assessed expression of IFN‐I in murine prion disease (ME7) and examined the contribution of the IFN‐I receptor IFNAR1 to disease progression. The data indicate a robust IFNβ response, specifically in microglia, with evidence of IFN‐dependent genes in both microglia and astrocytes. This IFN‐I response was absent in stimulator of interferon genes (STING −/− ) mice. Microglia showed increased numbers and activated morphology independent of genotype, but transcriptional signatures indicated an IFNAR1‐dependent neuroinflammatory phenotype. Isolation of microglia and astrocytes demonstrated disease‐associated microglial induction of Tnfα, Tgfb1, and of phagolysosomal system transcripts including those for cathepsins, Cd68, C1qa, C3, and Trem2, which were diminished in IFNAR1 and STING deficient mice. Microglial increases in activated cathepsin D, and CD68 were significantly reduced in IFNAR1 −/− mice, particularly in white matter, and increases in COX‐1 expression, and prostaglandin synthesis were significantly mitigated. Disease progressed more slowly in IFNAR1 −/− mice, with diminished synaptic and neuronal loss and delayed onset of neurological signs and death but without effect on proteinase K‐resistant PrP levels. Therefore, STING‐dependent IFN‐I influences microglial phenotype and influences neurodegenerative progression despite occurring secondary to initial degenerative changes. These data expand our mechanistic understanding of IFN‐I induction and its impact on microglial function during chronic neurodegeneration. Main Points: Microglial IFN‐I during chronic neurodegeneration is STING‐dependent. Microglial phagolysosomal, complement and prostaglandin pathways are suppressed in IFNAR1‐/‐ mice. Synaptic & neuronal degeneration and motor decline are slowed in IFNAR1‐/‐ mice.